An Effectiveness Analysis of Corporate Social Responsibility of Empowerment Program in Terminal BBM Pertamina Siantar - Muhammad Umar Maya Putra; Ami Dilham (Proceedings of AICS - Social Sciences, 2017)
The purpose of this research is to describe effectiveness of the Corporate Responsibility Program (CSR) that has been implemented by Terminal BBM Pertamina Pematang Siantar. The type of this research is descriptive by using qualitative approaching. The effectiveness analyze of CSR which contains of two empowerment indicators: first accuracy of implementation of the mechanic motorcycles training with the participants from 16 mechanic motorcycles among Siantar and the second is planting trees for green area with the participants from 9 Adiwiyata Schools. According to the result of research done by using interview, observation and documentation so the researcher can conclude that effectiveness of empowerment program in the participants both micro, small enterprises and school committee growth have run effectively as well as the conclusion for objectives in the empowerment program can be proved from each indicator of the effectiveness. The recommendation for empowerment by Terminal BBM Pertamina Siantar is to evaluate the results of the training empowerment program that has been given for mechanic motorcycles as well as the improvement of planting trees for green area for sustainable development.